132k views
0 votes
Use your graphing calculator to determine if the equation appears to be an identity or not by graphing the left expression and right expression together. If so, verify the identity. If not, find a counterexample. sec x + cos x = tan x sin x

User Jhonsore
by
5.2k points

1 Answer

6 votes

Answer:


(sec x)+(cos x)=(tan x)*(sin x)\\identities\\(sec x)= 1/cos x\\(tan x)=sin x/cos x\\\\and\\(cos x)^(2)+(sin x)^(2)=1\\(cos x)^(2)=1-(sin x)^(2)\\\\(1/cos x )+(cos x) = (sin x)*(sin x)/(cos x)\\ [(1/cos x)+(cos x)]*(cos x)=(sin x)^(2)\\\\1+(cos x)^(2)=(sin x)^(2)\\1+1-(sin x)^(2)=(sin x)^(2)\\2=2*(sin x)^(2)\\2/2=(sin x)^(2)\\1=(sin x)^(2)\\\\This is not true ,so\\(sec x)+(cos x)\\eq (tan x)*(sin x)

User Tomikiss
by
6.2k points